Exploring Natural Medicinal Plants for Novel Bcl-2 Inhibitors: In Silico Drug Design and Computational Interaction Mechanism for Anti-Cancer Activity - AL-SHUAEEB, Riyadh Ahmed Atto; Abbas, Ali Hussein; Tawfeeq, Mustafa Fayez; Abood, Sattar Jabir (Tikrit Journal of Pharmaceutical Sciences, 2024)
The disturbance of typical cellular programmed cell death, known as apoptosis, constitutes a distinctive feature across all categories of malignancies. This maladjustment of apoptosis has the potential to result in diverse pathological states such as cancer, autoimmune illnesses, and neurodegenerative disorders. The regulation of apoptosis hinges upon proteins affiliated with the BcL-2 family, which possess the capacity to either foster or impede this progression. The exaggerated expression of anti-apoptotic proteins (Bcl-2, Bcl-xL, and Mcl-1) has been linked to the sustenance, proliferation, and advancement of tumors. Lately, there has been a surge of interest in investigating small compounds and peptides that possess the ability to bind to the BH3 binding pocket of these proteins, as they exhibit promising potential as agents against cancer. Initially, the primary emphasis in the development of anti-cancer agents targeting this protein family was centered on suppressing Bcl-2. However, the precise mechanisms of drugs specific to Bcl-2 and their impacts have not been fully clarified through computational approaches. By conducting a molecular docking analysis against the Bcl-2 protein (PDB ID: 4LVT), out of the 8450 phytomolecules, 6742 compounds were effectively docked with Bcl-2, displaying docking scores ranging from -7.22 kcal/mol to +5.54 kcal/mol. Further investigation employing structure-based molecular docking (SB-MD) and ADMET (absorption, distribution, metabolism, excretion, and toxicity) profile analysis led to the identification of several plant-derived compounds, such as “Norepinephrine, Australine, Calystegine B, 7,7 A-Diepialexine, and Alpha-Methylnoradrenaline” which exhibited strong binding to the active site residues of Bcl-2. In summary, these phytocompounds show promise as potential molecules against the Bcl-2 protein (4LVT) and warrant further validation through “in vitro and in vivo” experiments.